2017
DOI: 10.1186/s13014-017-0906-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential dosimetric benefits of adaptive tumor tracking over the internal target volume concept for stereotactic body radiation therapy of pancreatic cancer

Abstract: BackgroundRadiotherapy for pancreatic cancer has two major challenges: (I) the tumor is adjacent to several critical organs and, (II) the mobility of both, the tumor and its surrounding organs at risk (OARs). A treatment planning study simulating stereotactic body radiation therapy (SBRT) for pancreatic tumors with both the internal target volume (ITV) concept and the tumor tracking approach was performed. The two respiratory motion-management techniques were compared in terms of doses to the target volume and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…If the movement of tumor and organs were ignored during treatment planning, the target dose would be insufficient while the OARs dose would exceed the dose constraint, leading to a decline in the therapeutic effect (21). The AS 20 and VS 20 were the fusion of the AS and VS with 20 phases, respectively, and the contouring of AS 20 and VS 2 covered the motorial range of the AS and VS during the cardiac cycle, which was relatively safe and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…If the movement of tumor and organs were ignored during treatment planning, the target dose would be insufficient while the OARs dose would exceed the dose constraint, leading to a decline in the therapeutic effect (21). The AS 20 and VS 20 were the fusion of the AS and VS with 20 phases, respectively, and the contouring of AS 20 and VS 2 covered the motorial range of the AS and VS during the cardiac cycle, which was relatively safe and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…The reported improvements in normal tissue irradiation reflect ability to deliver treatment using tracking on a gantry-based linac with reduced PTV size compared to the standard ITV approach. If this technique were to be applied for the treatment of lung and pancreatic cancer, the PTV could be reduced by up to 40% and 17%, respectively [92,93].…”
Section: Advanced Motion Management: Trackingmentioning
confidence: 99%
“…Karava et al have recently estimated respiratory-induced pancreatic motion in 12 patients using 4D-CT: mean displacement of 2 mm in antero-posterior (AP), 4.8 mm in inferior-superior (IS) and 1.3 mm in left-right (LR) direction were reported, values that can be hardly managed by the usual target margins. Other authors reported pancreatic movements up to 23 mm in IS, 11 mm in AP and 7 mm in LR directions [1315].…”
Section: Introductionmentioning
confidence: 99%